Blaming Culture Perceptions and Nurses' Attitudes in Reporting Medication Error Incidents in Hospital - Sulastri; Salam, Ainul Yaqin; Abidin, Zainal (Al-Hijrah Indonesia, 2023)
Background: Patient safety is an important issue for every country that provides health services, regardless of health services using private or government funding methods. Purpose: This research aims to determine the relationship between perceptions of blaming culture and Nurses' Attitudes in Reporting Medication Error Incidents at Tongas Regional Hospital, Probolinggo. Methods: This research uses a correlational analytical design with a cross-sectional approach. A sample amount 61 respondents obtained using a purposive sampling technique. The instrument used was the blaming culture perception questionnaire adapted from HSOPC, developed by AHRQ 2016. Meanwhile, the nurse attitude questionnaire in reporting medication error incidents had gone through the validity and reliability testing stage with Cronbach's alpha value was 0.876 by previous researchers, and the analytical test used in this research was the Spearman rho test. Results: The Spearman's rho analysis test shows a value of α<0.05, namely (0.000) which means that there is a relationship between the perception of Blaming Culture and the attitude of nurses in reporting medication error incidents at the Tongas Regional Hospital, Probolinggo. Conclusion: Professionalism and strong work culture must be emphasized through standard work behavior, forming solid teamwork, good communication in the work environment, and the involvement of management in taking the initiative to provide ongoing training and motivation to create awareness of the importance of patient safety culture.